(untitled) (Research, Society and Development, 2022)
The β-alanine is a non-essential amino acid and currently has been highlighted in the supplements industry because of its ergogenic potential, which is characterized by any artifice used to improve sports performance. This is because this supplement has the ability to stimulate the synthesis of muscle carnosine, a dipeptide formed by a combination of two amino acids, β-alanine and histidine, promoting an increase in strength and an improvement in sports performance. When supplemented, β-alanine causes paresthesia, which is characterized by a temporary tingling sensation in some regions of the body. Therefore, this research sought through a cross-sectional and descriptive study, to observe whether the paresthesia induced by the consumption of supplements based on or containing ß-alanine, may somehow be related to the perception of increased strength and improved performance in bodybuilding practitioners. The trial included 42 people, bodybuilders, who ingest supplements based on or containing β-alanine, residents in the Federal District. Data collection was performed via digital questionnaire published in the following social networks: Instagram, Facebook, Whatsapp, and Telegram, containing variables of gender, age (18 to 50 years old), frequency of physical activity, consumption of β-alanine, perception of paresthesia, and its benefits and/or harms, if any, during training. From the answers of the volunteers, it was possible to notice that the perception of paresthesia increased the motivation to train and improved sports performance, and it is possible to conclude that the paresthesia resulting from β-alanine supplementation has a possible ergogenic effect.